High-Speed Rail Opening and Green Innovation—Evidence From China - Yu, Xiaolin; Wan, Kai (Frontiers in Environmental Science, 2022)
Significant progress have been achieved in the construction of transportation infrastructure of China, forming a high-speed rail network with considerable scale and high operation speed. Against the backdrop of China’s current keynote on “carbon peaking” and “carbon neutrality”, the ability of high-speed rail, as a modern, green mode of transport, has become a key force in promoting green technological innovation and maintaining sustainable economic development. This paper, therefore, focuses on the relationship between the opening of high-speed rail and urban green innovation and the mechanisms behind it. This study, utilizing the panel data of Chinese cities from 2000 to 2018, and taking the opening of high-speed rail as a quasi-natural experiment, focuses on the impact and mechanism of the opening of high-speed railway on urban green innovation by using the double difference space Durbin model. This study figures out that high-speed rail plays a significant role in promoting urban green innovation, and the spatial spillover effect is substantial. The results of the heterogeneity test indicates that high-speed rail can enhance urban green innovation in non-resource-based cities. The impact mechanism of high-speed railway on urban green innovation mainly comes from the flow of innovative personnel and capital, the strategic of local governments to strengthen environmental regulations so as to improve regional advantages, Furthermore, this paper also indicates that high-speed rail has an inverted U-shaped trend in promoting urban green innovation, and the optimal radius is 200km from the nucleus city.